The effect of time on packed cell volume following packed red blood cell transfusion in anemic dogs. Issue 2 (29th October 2020) - Morris, Jennifer L.; Bloch, Christopher P.; Brabson, Tamera L.
Abstract: Objective: To compare the PCV at several timepoints following packed red blood cell (pRBC) administration to anemic dogs and to assess if underlying cause of anemia or regenerative status significantly affects these measurements. Design: Prospective, observational study from November 2016 to October 2017. Setting: A small animal emergency and specialty hospital. Animals: Forty‐six anemic client‐owned dogs that received a total of 50 pRBC transfusions for management of anemia. Interventions: Blood was collected, and a PCV was obtained prior to pRBC transfusion ( T 0), immediately after ( T 1), 30 minutes after ( T 2), 1 hour after ( T 3), 2 hours after ( T 4), and 4 hours after ( T 5) the transfusion. Underlying causes of anemia were classified as hemorrhage, hemolysis, and ineffective erythropoiesis. Dogs were also categorized in regard to regenerative status of anemia and the presence or absence of expected continued blood loss or destruction. Measurements and Main Results: The mean PCV at T 0 was 0.15 L/L (15%). After administration of a pRBC transfusion, the mean PCV at T 1 was 0.28 L/L (28%). For all other timepoints ( T 2, T 3, T 4, and T 5), the mean PCV was 0.27 L/L (27%). The PCV did not change significantly over time post‐transfusion ( P = 0.184), and no pairwise combinations of times differed significantly (paired t ‐tests; P > 0.05 for all). When dogs were categorized via regeneration status and continued blood loss or hemolysis, results were consistent. Conclusions: There was no significant change in PCV from the value obtained immediately after pRBC transfusion up to 4 hours post‐transfusion in dogs with several different causes of anemia. These results suggest that obtaining a PCV immediately after administering a pRBC transfusion to an anemic dog may be just as reliable as obtaining a measurement 2 hours after the transfusion. This remains true for dogs with expected continued red blood cell loss or destruction.